Intestinal decontamination with rifaximin attenuates LSEC dysfunction and liver fibrosis in mice - Tingting Su; Sanchuan Lai; Hongtan Chen (PLoS ONE, 2026)
Background The gut microbiome plays a pivotal role in the development and progression of liver disease. Liver sinusoidal endothelial cells (LSECs), as the first hepatic barrier exposed to blood from the portal circulation, may be influenced by gut-derived microbiota and their byproducts. This study aimed to investigate the interaction between gut microbiota and LSECs and to clarify how this interaction impacts the progression of liver cirrhosis. Methods Liver cirrhosis was induced by carbon tetrachloride (CCl 4 ) injection and bile duct ligation (BDL). CCl 4 and BDL mice were administered rifaximin. The primary LSECs were isolated from mice and treated with LPS. 16S rRNA sequencing was conducted to examine changes in the gut microbiota of cirrhotic mice following rifaximin treatment. Results Rifaximin attenuated liver fibrosis and LSEC dysfunction in CCl 4 and BDL mice. Liver cirrhosis induced remarkable changes in the gut microbiome while rifaximin treatment could partially reverse these alterations. Serum lipopolysaccharides (LPS) level was elevated in cirrhotic mice, while reduced following rifaximin treatment. Furthermore, LPS treatment could induce LSEC dysfunction by inhibiting eNOS mRNA expression, which was attenuated by TLR4 inhibitor, indicating that TLR4 signaling was involved in LPS-induced LSEC dysfunction. Conclusions Intestinal microbiota dysbiosis allows more LPS to enter the portal circulation, which may in turn exacerbate LSEC dysfunction and liver fibrosis. Intestinal decontamination with rifaximin improves LSEC function and alleviates liver fibrosis, a process linked to the reconstruction of the gut microbiome and a reduction in gut-derived LPS.